The substance of climate: Material approaches to nature under environmental change. (5th September 2018) - O'Reilly, Jessica
Abstract : Climate change is at once immediately tangible and embodied—in hurricanes, droughts, and the expansion of tick and mosquito habitats, for example—and almost unimaginable from a human scale. Climate encourages us to think expansively, in terms of millennia, geological epochs, systems and patterns earthly in scope. Climate, through material and cultural processes, connects people to weather and the environment, particularly in timescales beyond the human lifetime—though some changes occur rapidly, visibly, and spectacularly. This review seeks to understand how people mediate between climate change at once lived and unfathomable. I propose that people do this through interactions with nature as material objects and earthly processes. That is, there is a substance to climate that is sometimes erased from abstract models and political debates. This article considers the substance of climate through three analytical frames: (a) matter and substance, (b) lively nonhuman nature, and (c) experience and embodiment in science and policy. The materiality of climate allows us to consider the scientific and environmental impacts of climate change immediately alongside the power dynamics that enable and can solve this problem. This article is categorized under: Trans‐Disciplinary Perspectives > Humanities and the Creative Arts Social Status of Climate Change Knowledge > Sociology/Anthropology of Climate Knowledge Abstract : Climate change is both nearly unimaginable as well as intimate and embodied. This article explores how physical, material nature helps us understand the changing global environment.